2011
DOI: 10.1242/dev.068049
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 function during Ciona intestinalis neuronal development includes extensive interaction with the Notch signaling pathway

Abstract: SUMMARYThe nervous system-enriched microRNA miR-124 is necessary for proper nervous system development, although the mechanism remains poorly understood. Here, through a comprehensive analysis of miR-124 and its gene targets, we demonstrate that, in the chordate ascidian Ciona intestinalis, miR-124 plays an extensive role in promoting nervous system development. We discovered that feedback interaction between miR-124 and Notch signaling regulates the epidermal-peripheral nervous system (PNS) fate choice in tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 62 publications
8
70
0
Order By: Relevance
“…Of note, these two transcripts were not identified as miR-132 targets by HITS-CLIP in murine brain (8). MicroRNA-124 targets Ctdsp1 and PTBP1-both identified in this screen-have known roles in the embryonic development of the central nervous system in chick and mouse, as well as the nervous system development in Ciona intestinalis (50)(51)(52). The top candidate target in our miR-124 screen was RhoG, which showed an ∼20-fold enrichment.…”
Section: Discussionmentioning
confidence: 85%
“…Of note, these two transcripts were not identified as miR-132 targets by HITS-CLIP in murine brain (8). MicroRNA-124 targets Ctdsp1 and PTBP1-both identified in this screen-have known roles in the embryonic development of the central nervous system in chick and mouse, as well as the nervous system development in Ciona intestinalis (50)(51)(52). The top candidate target in our miR-124 screen was RhoG, which showed an ∼20-fold enrichment.…”
Section: Discussionmentioning
confidence: 85%
“…Siphon regeneration involves the regrowth and/or differentiation of severed nerve tracts (Auger et al, 2010). Since Notch signaling was previously shown to be involved in central and peripheral nervous system development in ascidian embryos and larvae (Akanuma et al, 2002; Pasini et al, 2006; Hudson et al, 2007; Chen et al, 2011), the possible function of the Notch pathway during adult neural regeneration would be an important subject for future study. Furthermore, during the Ciona life span, the capacity for regeneration continuously declines until it is compromised near the end of life (Dahlberg et al, 2009; Auger et al, 2010; Jeffery, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activity of Hedgehog signaling has been found to be regulated by several miRNAs. Studies have shown that miR-212, miR-214, miR-196, and miR-17-92 cluster could regulate Hedgehog signaling [24][25][26][27], suggesting that these miRNAs could participate in the development of pancreas.…”
Section: Mirna-regulated Signaling Pathways In Pancreas Developmentmentioning
confidence: 99%